User resistance factors in post ERP implementation - Salih Mahmoud, Sayed Haider (2012)
Enterprise resource planning (ERP) systems are becoming mature technologies to support inter- and intra-company business processes. However, one of the factors frequently cited as the major reason for the failure of ERP system in post implementation is “User Resistance”. ERP implementation doesn’t finish after Go-Live, instead the real test of system starts when user begins using the system. The main purpose of this study is to investigate user resistance factors in ERP post implementation stage and the influence between the factors associated with the research model, then to provide recommendations and guideline to avoid user resistance in ERP post implementation. To achieve this objectives quantitative method were conducted with 95 ERP end users. Correlation analysis is used to investigate the influence between user resistances as well as mean, std. deviation and rank. The result shows Resistance due to change, Change in Job content, User Expectations, Increased efforts, Lack of Education and User training, Usability issues and resistance to technology, Lack of user involvement in the development process, and Lack of communication between top management and end users are the factors behind user resistance. Recommendations and guideline to avoid user resistance in ERP post implementation are also presented. An equally important future direction is a psychological understanding of the users’ perspectives, Attitude strength, Attitude structure, and Resistance to change. For the user, there may be negative perceptions towards the ERP systems and the changes; however, the attitude strength and structure has not been examined. The benefits and outcomes of this study shall aid organizations to overcome user resistance in post ERP implementation.